Validation and Application of the LS/CMI in Nebraska Probation - Jimenez, Alisha Caldwell (Criminal justice and behavior, 2018)
This study examined the validity of the Level of Service/Case Management Inventory (LS/CMI), as probation officers in the state of Nebraska use the tool. Study 1 evaluated the predictive validity of the LS/CMI by examining 19,344 probationer records over a 5.5-year period (January 2007-July 2013), and found that the LS/CMI total risk score demonstrated moderate predictive validity. Consistent with past findings, logistic regression showed that the total risk score predicted recidivism (return to probation) differently for nonminorities than for minorities. Furthermore, minorities scored higher than nonminorities on seven of the eight criminogenic factors. Study 2, a true randomized experiment, explored probation officer bias as an explanation for these findings, and found that training increased officers’ ratings of scores in some LS/CMI domains and decreased ratings in others. Most importantly, there was no evidence that officers demonstrated racial bias in administering the LS/CMI survey when scoring Black versus White target clients.